Avaliar o processo de transferência de conhecimento e tecnologia na disciplina de Técnicas de Gestão Industrial - Ditkun, Sérgio (2017)
The objective of this study was to evaluate the process of knowledge and technology transfer in the discipline of industrial management techniques through industrial management techniques as the transfer tool itself. First, a questionnaire was prepared with the best 45 management techniques found in the literature. The method used was Methodi Ordinatio. At the beginning of the Industrial Management Techniques classes, in March 2016, the 45 chosen techniques were given to some students to select, in their opinion, the 10 most important management techniques, and then it was also asked them to rank the techniques between 10 and 1, with 10 being the most important and 1 being the least important technique. The researched academics belong to the Graduate Program in Production Engineering of UTFPR - Ponta Grossa Campus. In total, 55 academics were researched, being 22 of the specialization group, 26 of the master and 7 of the PhD programm. From this sample, some scholars only study, while others also work. Then, the technology transfer process of the management techniques began using the methodology adopted by the Professor of the discipline. Once the classes were over, in June 2016, the research paper with the 45 management techniques was given again to the academics to rank the 10 practices they then considered the best. After comparing the answers of the two surveys, a roadmap was proposed so that the technology transfer tool would always be up to date with the best management practices.The main result was that there was a perception change of the ten best practices chosen, aswell as in the ranking relation of the first measurement, showing that there was a technology transfer in the discipline.A great contribution of this work to the University, especially for the Industrial Management Techniques discipline was the validation of the methodology and the technology transfer tool.